The Influence of Digital Storytelling, Local Cultural Authenticity, And Social Media Content Quality On UMKM Product Purchase Decisions In Sampit City - Wahyuni, Wahyuni; Riyadi, Andri; Muamar, Muamar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to analyze the influence of Digital Storytelling, Local Cultural Authenticity, and Social Media Content Quality on MSME Product Purchasing Decisions in Sampit City, East Kotawaringin Regency, Central Kalimantan Province. The background of this study is based on the phenomenon of the increasing role of digital media in marketing local products, amidst the strong current of globalization and penetration of information technology. Although studies on digital marketing have developed, the integration of local cultural aspects in MSME digital storytelling strategies in the region is still rarely discussed. This study uses a quantitative approach with a survey method of 150 respondents or consumers of MSME products in Sampit City. Data were collected through a Likert scale questionnaire (1–4) and analyzed using multiple linear regression using SPSS 26. The results show that digital storytelling, local cultural authenticity, and social media content quality have a significant influence on consumer purchasing decisions. The contribution of this study lies in the integration of local culture in digital marketing strategies that are still rarely studied. Therefore, these findings provide theoretical contributions by strengthening the integration of digital marketing concepts based on local wisdom, as well as practical implications for MSMEs in designing more effective marketing strategies.